Interaction of fatty acids, acyl-CoA derivatives and retinoids with microsomal membranes: effect of cytosolic proteins. - Catalá, Ángel (1993)
This paper reviews characteristics of microsomal membrane structure; long chain fatty acids, acyl CoA derivatives, retinoids and the microsomal formation of acyl CoA derivatives and retinyl esters. It is analyzed how the movement of these molecules at the intracellular level is affected by their respective binding proteins (Fatty acid binding protein, acyl CoA binding protein and cellular retinol binding protein). Studies with model systems using these hydrophobic ligands and the lipid-binding or transfer proteins are also described. This topic is of interest especially because in the esterification of retinol the three substrates and the three binding proteins may interact.